Socioeconomic Determinants of the Labor Market Structure of the San Juan Site of the City of Manta - Guillén, Yaritza (2021)
The labor market in Latin America is affected by two major problems: the scarce creation of job sources that consequently encourages unemployment, self-employment and informality; and, job insecurity, which leads to jobs that do not guarantee the minimum social benefits to face social risks, reducing job stability and increasing the vulnerability of society that faces the loss of well-being. underemployment are two phenomena that affect a large part of the population of developing countries; informality refers to the low quality of employment from the point of view of the demand for labor, and includes workers in companies with low productivity; While underemployment refers to the quality of employment from the viewpoint of the job offer, including workers who are not satisfied with the job they have (Uribe, Ortiz, & García, 2008). , in recent years the generation of jobs in the informal sector has been increasing, this as a consequence of the economic slowdown that affected the entire Latin American and Caribbean region in 2015 and that affected internal production, derived from the fall in oil prices; In addition, the consequences of the earthquake of April 16, 2016 and the growing flow of immigration, mainly from Colombia and Venezuela (Olmedo, 2018)